2021
DOI: 10.1155/2021/1286570
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effectiveness of Three Different Acupuncture Methods for TMD-Related Pain: A Randomized Clinical Study

Abstract: Purpose. This study aimed to compare the effectiveness of three acupuncture methods for temporomandibular disorders- (TMDs-) related pain. Materials and Methods. Different locations of pain, according to DC/TMD clinical assessment, were considered: temporomandibular joint (TMJ), masticatory muscles, head, and neck. Sixty patients were assigned randomly to one of three treatment groups (20 patients in each): group BA received body acupuncture, group EA received electroacupuncture, and group CA received acupunct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…A recent study by Yap et al reported a higher level of psychological disturbance and poor quality of life in patients with moderate-to-severe TMD [5,6]. Acupuncture has been shown to be effective in reducing pain and improving quality of life in TMD patients [7].…”
Section: Transverse Malocclusionsmentioning
confidence: 99%
“…A recent study by Yap et al reported a higher level of psychological disturbance and poor quality of life in patients with moderate-to-severe TMD [5,6]. Acupuncture has been shown to be effective in reducing pain and improving quality of life in TMD patients [7].…”
Section: Transverse Malocclusionsmentioning
confidence: 99%
“…Acupuncture therapy (AT) is an effective method of pain management, especially for pain of musculoskeletal origin, including TMD [13,14]. Several clinical studies analyzed the effects of different types of acupuncture treatments on pain related to TMD and proven its effectiveness, especially for pain of muscular origin, such as myalgia and myofascial pain [15][16][17]. In the OP field, classic somatic AT is the most investigated AT method, followed by laser acupuncture, electroacupuncture and several microsystems AT methods, such as ear, scalp, mouth, and fingers [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…16,17 Although to a lesser degree, acupuncture has shown some evidence in the attenuation of neck pain, dental-associated pain, and pain associated with temporomandibular disorders. 14,18,19 Acupuncture has been tested on pain relief associated with arthritic conditions, which include osteoarthritis and rheumatoid arthritis, and on depressive symptoms that are associated with posttraumatic stress disorder, generally with relatively little to no demonstrated positive effect. [20][21][22] Multiple studies have now demonstrated that the prevalence of acupuncture use in the USA, in recent decades, has increased massively.…”
Section: Introductionmentioning
confidence: 99%